Immunoregulatory Effects of Subcutaneous Immunotherapy on Lymphocyte Subgroups and Cytokines in Children with Asthma - Yu-ting He; Ying Zhou; Qi Shao; Cong Gan; Meng Chen; Yu-ling Bao; Hai-yan Gu; Shu-lan Zhang; Yubao Cui; Man Tian (Journal of Immunology Research)
Objective. Asthma is a syndrome that incorporates many immune phenotypes. The immunologic effects of subcutaneous immunotherapy (SCIT) exerts on allergic asthma remain still largely unknown. Here, we investigated the effects of SCIT on cytokine production and peripheral blood levels of lymphocyte subtypes in children with mite-induced moderate and severe allergic asthma. Methods. The study included 60 kids with mite-induced allergic asthma from 5 to 10 years old. All subjects had received antiasthmatic pharmacologic for 3 months at baseline. Half of the children were treated with SCIT combined with pharmacologic treatment named the SCIT group and the other half only with pharmacologic therapy named the no-SCIT group. Total asthma symptom score (TASS) and total medication score (TMS) were recorded. Flow cytometry was used to identify lymphocyte subtypes: type 2 innate lymphocytes (ILC2s), type 1 (Th1) and type 2 (Th2) helper T cells, T helper 17 (Th17) cells, and regulatory T (Treg) cells. ELISA, flow cytometry, and cytometric bead array were used to assess cytokines IL-13, IFN-γ, IL-4, IL-17, and TGF-β, at baseline and 3 and 6 months after study treatment in both groups of patients. Results. Both groups can significantly improve clinical symptoms in children with asthma. SCIT can significantly reduce asthma medication after 6 months of treatment. SCIT induced a significantly higher and progressive reduction in ILC2 percentage and IL-13 levels after 3 and 6 months of treatment compared with baseline and compared with no-SCIT patients. Significant differences were detected in the Th1/Th2 cell ratio and IFN-γ/IL-4 cytokine ratio between groups after 6 months of treatment. Similarly, the Th17/Treg ratio and IL-17/TGF-β ratio in the SCIT group were much lower than those in the no-SCIT group after 3-6 months of treatment. Conclusion. SCIT is a promising option to reduce the percentage of ILC2 and regulate Th1/Th2 and Th17/Treg immune balance in the peripheral blood of children with asthma.